Implementasi Kebijakan Retribusi Parkir Badan Jalan di Kota Pekanbaru - Ema Fitri Lubis; Rio Sundari; Rosmayani Rosmayani; Zilfi Purnama Rahmi (Jurnal Ilmu Sosial dan Ilmu Politik)
In urban areas with high levels of mobility in driving, the high push for urbanization and the rapid demand for vehicles have resulted in additional parking spaces. Parking management policies play a major role in developing strategies to improve mobility in urban areas in Indonesia. One of these cities is the kota Pekanbaru. This research aims to analyze what factors hinder the implementation of the on-street parking levy policy in Pekanbaru City. The method used in this research is descriptive qualitative, collecting data by means of interviews, observation and documentation. The research results show that research using indicators of size and policy objectives is in the category of not running well in relation to the determined tariff rates. In terms of resources, the facilities and services received by parking users are felt to be less than optimal. The characteristics of implementing agents include obstacles such as weak supervision carried out by the kota Pekanbaru parking UPT. Indicators of attitudes or tendencies of implementers include coordination between the Transportation Service and UPT. Parking as a technical implementer, parking attendant and involving partners, namely the third-party PT. Yabisa Sukses Mandiri (YSM). Indicators of communication between organizations and implementing activities are felt to be less than optimal in providing services to parking service users. However, in terms of policy implementation activities, it has gone well. Furthermore, the economic, social and political environmental indicators have been running well in terms of economic carrying capacity, but in terms of the socio-political environment it has not been running optimally.